2009
DOI: 10.1186/1472-6831-9-35
|View full text |Cite
|
Sign up to set email alerts
|

The emerging dental workforce: long-term career expectations and influences. A quantitative study of final year dental students' views on their long-term career from one London Dental School

Abstract: BackgroundResearch into the motivation and expectations of the emerging workforce and their short-term expectations has already been reported with a view to informing professional and policy decisions. The objective of this component of the research programme was to examine the long-term goals and perceived influences on final year dental students' professional careers.MethodsUnivariate analysis of a self completed questionnaire survey of all final year dental students from King's College London, comprising qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
96
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 15 publications
10
96
2
4
Order By: Relevance
“…The minority of students (2%) who intend providing only NHS dental treatment supports previous findings, 5 possibly due to the perceived lack of financial reward, and the need to repay any amassed student debt. It has been suggested previously 4 that if the NHS took into account factors that dental students felt were important, such as increasing funding levels, spending more time with patients and using modern materials they would be more likely to provide treatment on the NHS. Whilst the majority intend on providing both NHS and private dental treatment, it is the amount of time they spend on providing NHS treatment, rather than simply the numbers, that will have an impact on access for patients and therefore this needs to be considered in the future planning of dental accessibility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The minority of students (2%) who intend providing only NHS dental treatment supports previous findings, 5 possibly due to the perceived lack of financial reward, and the need to repay any amassed student debt. It has been suggested previously 4 that if the NHS took into account factors that dental students felt were important, such as increasing funding levels, spending more time with patients and using modern materials they would be more likely to provide treatment on the NHS. Whilst the majority intend on providing both NHS and private dental treatment, it is the amount of time they spend on providing NHS treatment, rather than simply the numbers, that will have an impact on access for patients and therefore this needs to be considered in the future planning of dental accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontics was the most popular choice of subject (40%), especially from females (47%), supporting previous findings. 4 However, restorative dentistry is now a less popular choice compared to previous findings when it was found to be as popular as orthodontics. 4 Previous studies have also found an increase in the number of female dentists specialising and significant gender differences within specialities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations